Emotional intelligence and demographic factors: Moderating effects in service recovery strategy - Chokpiriyawat, Thanuset; Siriyota, Kampanat (Edelweiss Applied Science and Technology, 2024)
This study highlights the role of emotional intelligence, gender, income, and residence area on the relationship between brand image, service recovery strategy, and satisfaction. The multistage with purposive sampling method has recruited 600 samples of private hospital services in Thailand. Self-administered online questionnaires via Google Forms were used to collect the data online. Confirmatory factor analysis and multigroup SEM have been used for hypothesis testing. The research explores emotional intelligence (EI), with lower emotional intelligence associated with more negative perceptions of social brand image. Lower income affects the symbolic and social image, influencing satisfaction with a service recovery strategy. The upcountry areas viewed experiential images more positively compared to those from urban regions. Gender did not significantly moderate these relationships. The study also highlights thatfactors do not substantially impact service recovery satisfaction but are still vital for effective communication and brand attachment. The results underscore the intricate dynamics of the various factors that shape consumer attitudes and behaviours toward service recovery strategy.